Program Kampus Mengajar sebagai Strategi Peningkatan Literasi Peserta Didik Sekolah Dasar - Septiyani, Kadek Asih; Faturrohmi, Dian; Izzatika, Amrina; Supriyadi, Supriyadi (Universitas Hamzanwadi, 2024)
This article discusses the strategy of the Teaching Campus program as an effort to increase literacy and numeracy in elementary school students. The main problem faced is the low level of literacy among students, which impacts their academic abilities and skill development. The aim of this research focuses on identifying the effectiveness of the Teaching Campus program in increasing student literacy and analyzing supporting and inhibiting factors in its implementation. The method used is descriptive-quantitative, with data collection through a Minimum Competency Assessment consisting of a pre-test and post-test. The assessment was carried out on 7 grade V elementary school students. The findings show that there is a significant increase in literacy skills among students after participating in the program, with an average pretest score of 52.85 and an average posttest score of 87.14. In addition, factors such as the involvement of student teachers and support from the school play an important role in the success of the program. This research confirms that the Teaching Campus program is effective in increasing the literacy of elementary school students. Recommendations for further development include increased training for student teachers and an emphasis on interactive teaching methods.